‘I’m not getting out of bed!’ The criminalisation of young people in residential care - Gerard, Alison (The Australian and New Zealand journal of criminology, 2019)
Evidence from both Australian and international jurisdictions show that children in residential care are over-represented in the criminal justice system. In the current study, we interviewed 46 professionals who had contact with young people in residential care settings in New South Wales, Australia. Our sample included police officers, residential care service providers, legal aid lawyers and juvenile justice workers, about their perceptions of the link between residential care and contact with the criminal justice system. Factors identified by the participants included the care environment itself, use of police as a behavioural management tool, deficient staff training and inadequate policies and funding to address the over-representation. These factors, combined with the legacy of Australia’s colonial past, were a particularly potent source of criminalisation for Aboriginal children in care.